Multifaceted Impact of Host C–C Chemokine CCL2 in the Immuno-Pathogenesis of HIV-1/M. tuberculosis Co-Infection - Ansari, A W.; Kamarulzaman, Adeeba; Schmidt, Reinhold E. (Frontiers in Immunology, 2013)
Active tuberculosis remains the leading cause of death among the HIV-1 seropositive individuals. Although significant success has been achieved in bringing down the number of HIV/ AIDS-related mortality and morbidity following implementation of highly active anti-retroviral therapy (HAART). Yet, co-infection of Mycobacterium tuberculosis (Mtb) has posed severe clinical and preventive challenges in our efforts to eradicate the virus from the body. Both HIV-1 and Mtb commonly infect macrophages and trigger production of host inflammatory mediators that subsequently regulate the immune response and disease pathogenesis. These inflammatory mediators can impose beneficial or detrimental effects on each pathogen and eventually on host. Among these, inflammatory C-C chemokines play a central role in HIV-1 and Mtb pathogenesis. However, their role in lung-specific mechanisms of HIV-1 and Mtb interaction are poorly understood. In this review we highlight current view on the role of C-C chemokines, more precisely CCL2, on HIV-1: Mtb interaction, potential mechanisms of action and adverse clinical consequences in a setting HIV/Mtb co-infection. Targeting common chemokine regulators of HIV/Mtb pathogenesis can be an attractive and potential anti-inflammatory intervention in HIV/AIDS-related comorbidities.